'Does it threaten the status quo?' Elite responses to British punk, 1976–1978. Issue 2 (13th April 2018) - Street, John; Worley, Matthew; Wilkinson, David
Abstract: The emergence of punk in Britain (1976–1978) is recalled and documented as a moment of rebellion, one in which youth culture was seen to challenge accepted values and forms of behaviour, and to set in motion a new kind of cultural politics. In this article we do two things. First, we ask how far punk's challenge extended. Did it penetrate those political, cultural and social elites against which it set itself? And second, we reflect on the problem of recovering the history and politics of moments such as punk, and on the value of archives to such exercises in recuperation. In pursuit of both tasks, we make use of a wide range of historical sources, relying on these rather than on retrospective oral or autobiographical accounts. We set our findings against the narratives offered by both subcultural and mainstream histories of punk. We show how punk's impact on elites can be detected in the rhetoric of the popular media, and in aspects of the practice of local government and the police. Its impact on other elites (e.g. central government or the monarchy) is much harder to discern. These insights are important both for enriching our understanding of the political significance of punk and for how we approach the historical record left by popular music.